The Electronic Component of Solid Fluoride Electrolytes (Metallurgy and Foundry Engineering, 2017)
The solid electrolytes based on sodium cryolite are present in aluminium electrolysers as frozen crystals formed on the side walls of the carbon lining (side ledge). Their main task is to protect the lining from the effect of liquid electrolyte and ensure temperature stabilization during the process of electrolysis. On the other hand, being electrically conductive, they can reduce the current efficiency. In this study, the value of the electronic component of the total conductivity of the solidified electrolytes of different compositions was determined. It was found that the highest electronic conductivity is exhibited by electrolytes containing both aluminium and calcium fluoride. However, the electronic component of the total conductivity is not high and reaches 0.1-2.3 mS/cm. Its share in the total conductivity of the solid multi-component electrolytes varies and, depending on their composition, is in the range of 1 ÷ 10%.